Communication strategy in increasing awareness of sate maranggi as a culinary icon of the nusantara - Tri Yuni Susilowati; Alifia Ananda Putri; Daniaka Sianson Gultom (Universitas Merdeka Malang, 2023)
The diversity of ethnics in Indonesia is an important asset of tourism. From Sabang to Merauke, this country has an impressive range of culinary assets which are often found different between every respective ethnicity. The acculturation of any part of the world's unique cuisine has made Indonesia’s cuisine considered one of the best. The culinary icon is a popular food in the respective territory. To become an icon, the food needs to be the symbol and has a unique advantage compared to the other place. A culinary icon is determined based on 3 criteria; they are the ease to get the ingredients, widely known by the locals, and the existence of professionals in the field (Fizriyani, 2017). The Ministry of Tourism has introduced 30 Indonesian culinary icons. Sate Maranggi, Purwakarta’s special, is there among the other 59 on the list. Unfortunately, there is still a quite significant number of people who admitted the unawareness of the existence of Sate Maranggi. This article will discuss the strategy to build awareness of the Sate Maranggi as one of the most important culinary icons. In order to reveal the condition and suggest further action, the author(s) were using qualitative method with in-depth interview approach. 40 Purwakarta residents picked through Random Sampling. The research concluded in the awareness of Purwakartans of the culinary’s status. However, they still need access to the appropriate information of the culinary. Although most of the Purwakarta residents were aware of the heritage status of Sate Maranggi, there were lack of channeling of the information distribution, since most of the awareness came from word of mouth. Ministry of Tourism, Purwakarta local government, and the local Sate Maranggi business owners better start to build the awareness through social media, where information are spreading faster and wider.